EXPERIMENTAL MODELING AND MEASUREMENT OF THERMAL CONDUCTIVITY OF SEDIMENTS CONTAINING METHANE HYDRATES - Duchkov A.D.; Kazantsev S.A.; Permyakov M.E.; Manakov A.Yu.; Ogienko A.G. (My University, 2006)
The authors of the present paper worked out and produced a device that allows us to model the samples of methane hydrate-containing rocks and to measure their thermal conductivity. Thermophysical parameters can be assigned to the most interesting characteristics of hydrate-containing sediments, because they determine the dynamics of temperature field that controls processes of the formation and decomposition of gas hydrates. In addition, there is good reason to believe that, based on measurements of thermal conductivity in situ, one can work out new geothermal methods for the discovery and evaluation of the gas hydrate content in the subsea sediments.